Identifikasi Manajemen Teknis Pemeliharaan Ternak Kambing di Kecamatan Bikomi Utara Kabupaten Timor Tengah Utara - Pasi, Maria Selfiana; Beyleto, Veronika yuneriati; Simamora, Ture; Sahala, Josua; Mau Diru , Oktovianus (Tropical Livestock Science Journal, 2025)
The purpose of this research is to identify the technical management of goat maintenance in Bikomi Utara District, North Central Timor Regency. This research was conducted from July to September 2024 in Banain A, Banain B, Banain C, Faenake, Sainoni, Tes, and Napan Villages, Bikomi Utara District, North Central Timor Regency. The research method used survey techniques and direct interviews with farmers based on the prepared questionnaire. The variables in this study are feed management, housing management, reproduction management, disease control management, and marketing management. The results of this study indicate that the technical management of goat maintenance includes feed management, with 90.9% providing feed 2 times/day, 84.8% frequency of providing drinking water is 1 time/day, the type of feed given is 56.6% grass + forage, the type of concentrate and frequency of providing concentrate is 71.7% never given, agricultural waste 50.5% is corn waste. The type of housing in this study is 84.8% dominated by group housing, the materials for making housing 85.9% come from local materials, with housing sizes of 0-10 m² being 28.3%, the frequency of cleaning the housing is 1 time/day 42.4%, the availability of feed and drinking water places 57.6% is not available, 100% no disinfectant spraying is available. Reproduction management 100% uses a natural mating system, handling of mothers giving birth and kids at birth is 97.0% handled by farmers, understanding of the signs of goats in heat 72.7% do not understand, understanding of the goat heat cycle 100% of farmers do not understand, 90.0% of farmers do not understand the duration of heat in goats. Disease control management 47.5% of livestock have never been affected by disease, livestock that are not treated amount to 55.6%, 64.6% of livestock are not given medicine, vitamin administration 88.9% of livestock are not given vitamins, the number of livestock that died due to illness 66.7% of livestock did not die due to illness. Marketing management 94.9% of livestock are sold in the market, with the purpose of selling livestock for household needs 41.4%, farmers sell their livestock only when needed, which is 96.0%.